Russia in the Reign of Aleksei Mikhailovich - Kotoshikhin, Grigorii Karpovich (De Gruyter, 2014)
The book presents the first English edition of "On Russia in the Reign of Aleksei Mikhailovich" by Grigorii Kotoshikhin. This is the only native source describing the character of the seventeenth-century Russian state and society. It offers a unique and detailed picture of the nature of Russian "autocracy", the life at the tsar's court, social mores of the nobles and commoners of those times, military affairs, diplomatic relations, etc. The book is a veritable ethnographic encyclopedia of early Russian life. With broad commentaries and supporting materials provided by the translator, Benjamin Uroff, and the editor, Marshall Poe, it provides an invaluable source for understanding XVII-century Muscovite Russia.